Cytotoxicity of orthodontic temporary anchorage devices on human periodontal ligament fibroblasts in vitro - Zhibin Chen; Manika Patwari; Dawei Liu (Wiley, 2019)
Abstract Objectives The objective of this study is to test cytotoxicity of four brands of commercially available orthodontic temporary anchorage devices (TADs). Setting and sample population Twenty‐four (six for each brand, i.e., Aarhus [AO]; Dual top [RMO]; Vector TAS [ORMCO]; and Unitek TAD [3M UNITEK]) TADs were tested. Materials and methods Twenty‐four (six for each brand, i.e., Aarhus [AO]; Dual top [RMO]; Vector TAS [ORMCO]; and Unitek TAD [3M UNITEK]) TADs were individually incubated in complete cell culture medium and shaken at a rate of 1.5 rpm at 37°C for 30 days to extract possible toxic substances in conditioned media (CM). To test cytotoxicity, human periodontal ligament fibroblasts were cultured and exposed to the CM for 24 hr, followed by the examinations of morphological changes, cell viability (MTT assay), and cell damage (lactate dehydrogenase [LDH] assay). Results No morphological changes were observed in any of the four brands of TADs compared with the negative control. LDH assay showed that none of the four brands of TADs caused significant cell damage after CM treatment compared with the negative control (P > .05). No significant differences were found between any of the four brands of TADs (P > .05). MTT assay showed similar results as did the LDH assay, except for a statistically significant difference found in the TADs from 3M UNITEK compared with the negative control (P = .047). Conclusions According to the International Standard Organization standards, except for the TAD from 3M, none of the other three brands of commercially available TADs (from AO, RMO, and ORMCO) exhibited significant cytotoxicity, suggesting their safe clinical applications.